Evaluation of hypolipidemic activity of ethanolic Extract of barleria cristata in alloxan Induced diabetic rats - P.KAVITHA (International Journal of Pharma and Bio Sciences, 2017)
Diabetes mellitus is a major degenerative disease in the world today affecting at least 15 million people. The plant Barleria cristata is popular in Tamilnadu and for it’s used in house hold remedies. It is traditionally known for its various properties and used to treat several ailments like anemia, toothache and cough. Root and leaves are used in the treatment of swelling and inflammation. The study was carried out to evaluate the hypolipidemic activity of 50% ethanolic extract Barleria cristata by inducing hyperglycemia with the help of alloxan in albino rats and various parameters such as serum glucose, liver glycogen, Glycosylated haemoglobin, lipid profiles were determined. Ethanolic extract showed significant (p<0.05) hypolipidemic activity by lowering the levels of total cholesterol, triglycerides, LDL and VLDL, and simultaneously increasing the levels of HDL in alloxan induced diabetic rats. The phytochemical constituents such as alkaloids, flavanoids and phenols present in the plant may be responsible for hypolipidemic activity and the results justify the use of Barleria cristata as a significant hypolipidemic agent in diabetic rats.